Ways of Mastering and Improving Practical Skills among Oral and Maxillofacial Surgeons in the System of Moscow Healthcare Department - V. A. Belchenko; I. V. Chantyr; K. D. Zavgorodnev (Здоровье мегаполиса)
Background. The surgical specialists, including oral and maxillofacial surgeons (OMFSs), must constantly acquire high professional competencies by expanding theoretical knowledge as well as by improving the skills to perform complex surgical interventions in the head and neck area. Current two-year residency program doesn’t provide adequate theoretical training with opportunities to practice all the necessary skills. Therefore, the task of healthcare managers and heads of continuing professional education (CPE) faculties at medical universities is to create the relevant conditions for elaborating advanced training programs. As a result, there emerged needs and prospects to develop up-to-date innovative educational and methodological activities.Objective. Improving the skills to perform surgical procedures among OMFSs in the system of Moscow Healthcare Department.Materials and methods. A survey of employees from the healthcare organizations of Moscow Healthcare Department were conducted in order to identify the skill level of OMFSs in performing basic surgical procedures. A practice-oriented education program with improving manual skills on cadaveric material was developed and approved based on the results of survey. Six practical dissection courses were held from November to December 2023 at the premises of the Interdisciplinary Training Center for Innovative Surgical Technologies of the State Budgetary Institution of Healthcare “L. A. Vorohobov City Clinical Hospital No. 67 of Moscow Healthcare Department”.Findings and discussions. An educational program “Features of the surgical procedures for post-traumatic defects and deformities of the bones of middle face region. Features of the surgical procedures on the parotid gland. Features of the surgical procedures on the oral and maxillofacial region in medical emergencies” was developed with a volume of 18 credits. The course participants included 54 OMFSs working at the healthcare organizations of Moscow Healthcare Department. The results of final testing showed that all 54 participants successfully completed the educational program. According to the data collected by questionnaires, the satisfaction of trained specialists with the quality of educational services was 9.54 points.Conclusion. The study has demonstrated that it is promising to organize the training of medical specialists within the CPE framework with the opportunity to improve practical skills on a cadaveric material at the premises of innovative training centers. Such training improves the systems of healthcare and CPE and minimizes the number of errors and complications in clinical practice, thereby increasing the effectiveness of treatment and the patient outcomes.